Modeling and Optimizing Buttermilk Concentration and Coagulation Temperature for Paneer Production - Chaudhary , Gaurav; Salaria, Ameeta; ARORA, SHALINI; Singh, A.K. (Indian Journal of Dairy Science, 2024)
This study explores the utilization of buttermilk, a significant byproduct of butter manufacture, in the production of paneer, a heat and acid-coagulated dairy product. Response Surface Methodology (RSM) was employed to investigate the impact of buttermilk addition (7.5-25.00%) and coagulation temperature (70-85°C) on various compositional parameters of paneer. The paneer yield ranged from 16% to 21%, while total solids, fat, protein, and lactose content varied from 40.5% to 50.5%, 21.0% to 32.5%, 10.1% to 18.8%, and 1.9% to 2.8%, respectively, at different buttermilk levels. Through optimization, it was found that replacing 13.99% of milk with buttermilk and coagulating at 85°C resulted in the production of paneer with enhanced nutritional quality. This study demonstrates an innovative and sustainable approach to improving the value of buttermilk and obtaining high-quality paneer with desirable nutritional attributes.